PENGARUH PEMBELAJARAN IPAS MELALUI PENDEKATAN COMPUTATIONAL THINKING BERBASIS SCRATCH TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KOMUNIKASI SISWA SEKOLAH DASAR - Eka Nugraheni, Dian; Anggoro, Subuh; Dyah Purwandari, Ristiana; Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian students' critical thinking skills remain low, reflected in the 2022 PISA results, where Indonesia ranked 69th of 80 countries, with only 0.9% of students reaching level 4–6 higher-order thinking questions in science. A diagnostic test given to 16 fourth-graders at SD Negeri 2 Kesenet, Banjarmangu, Banjarnegara, showed an average score of only 59, far below the mastery criterion, with students struggling to explain reasoning and analyze cause-and-effect relationships on the abstract topic of "Energy and Its Changes." This study examined the effect of Computational Thinking (CT) learning through Scratch on elementary students' critical thinking and communication skills. A quantitative Quasi-Experimental Posttest-Only Control Group Design involved 31 fourth-graders from two schools in one cluster selected through total sampling: 16 students in the experimental group, taught using CT through Scratch simulations, and 15 in the control group, taught using conventional picture-based media. Data were collected through essay tests and Likert-scale observation sheets, then analyzed using independent sample t-tests and Pearson correlation with SPSS. Results showed the CT-based Scratch approach significantly affected both critical thinking (p = 0.001, mean difference = 15.92) and science communication skills (p = 0.014, mean difference = 9.80). The correlation between the two variables was positive, strong, and statistically significant (r = 0.685, p = 0.001). These findings suggest CT-based Scratch learning effectively enhances critical thinking and communication skills, both separately and in parallel within individual students.